Notes on Crocus L. Series Flavi Mathew (Iridaceae) and a new species with unique corm structure - Çiftçi, Almila; Harpke, Doerte; Mollman, Rachel; Yildirim, Hasan; Erol, Osman (Phytotaxa, 2020)
Crocus asymmetricus (Iridaceae) is described as a new species endemic to the southern part of the Anatolian diagonal in Turkey. It is phylogenetically related to C. vitellinus and morphologically to C. antalyensis, but differs from these species in showing an asymmetric corm and a single point of root emergence. Both C. antalyensis and C. asymmetricus are illustrated and compared in this paper. A Bayesian phylogenetic tree of the nuclear rDNA ITS region confirms the affiliation of C. asymmetricus to C. ser. Flavi, and its close relationship to C. vitellinus. A new identification key to the species of C. ser. Flavi occurring in Turkey is also presented.